Applications of 2-deoxy-2-fluoro-D-glucose (FDG) in Plant Imaging: Past, Present, and Future - Fatangare, Amol; Svatoš, Aleš (Frontiers in Plant Science, 2016)
The aim of this review article is to explore and establish the current status of 2-deoxy-2-fluoro-D-glucose (FDG) applications in plant imaging. In present article, we review all the previous literature on its experimental merits to formulate a consistent and inclusive picture of FDG applications in plant imaging research. FDG is a [18F]fluorine labeled glucose analog in which C-2 hydroxyl group has been replaced by positron emitting [18F] radioisotope. FDG being a positron emitting radiotracer could allow for in vivo imaging. FDG mimics glucose chemically and structurally. Its uptake and distribution is found to be similar to that of glucose in animal models. FDG is commonly used as a radiotracer for glucose in medical diagnostics and in vivo animal imaging studies but rarely in plant imaging. Tsuji et al (2002) first reported FDG uptake and distribution in tomato plants. Later, Hattori et al (2008) described FDG translocation in intact sorghum plants and suggested that it could be used as a tracer for photoassimilate translocation in plants. These findings raised interest among other plant scientists which resulted in recent surge of research papers involving FDG as a tracer in plants. In total, there have been 7 studies describing FDG imaging applications in plants. These studies describe FDG applications ranging from monitoring radiotracer translocation to analyzing solute transport, root uptake, photoassimilates tracing, carbon allocation, or glycoside biosynthesis. Recently, Fatangare et al (2015) characterized FDG metabolism in plants which was a crucial aspect of understanding and validating FDG applications in plant research. Although all of the above studies significantly advanced our understanding of FDG translocation and metabolism in plants, it also raised new questions. Here, we take a look at the previous results cumulatively to form a comprehensive picture of FDG translocation, metabolism, and applications in plants. In conclusion, we summarize the current knowledge, discuss possible implications and limitations of previous studies, point out the open questions in the field, and comment upon the outlook of FDG applications in plants imaging.